An exceptional way to join two textiles: A textile fragment from Hisn al-Bab, Egypt - Kwaspen, Anne (Archaeological Textiles Review, 2020)
Since 2019, a research project has been ongoing on the many textile fragments that were excavated in Hisn al-Bab, near Aswan, Egypt (late sixth to early seventh century CE). Part of the study focuses on the determination of clothing fragments. Seams are an important feature for identifying garments. An investigation of these features revealed that one of Hisn al-Bab’s textile fragments provides evidence for an unusual way of joining two woven textiles without using sewing techniques.